Eddy covariance measurement-based differences in annual evapotranspiration between forests and grasslands in China - Fan, Renxue; Sun, Mingyu; Zhu, Xianjin; Wang, Qiufeng (Frontiers in Plant Science, 2022)
Annual evapotranspiration (AET), the total water vapor loss to the atmosphere during a year, is a vital process of water cycles and energy cycles. Revealing the differences in AET values and spatial variations between forests and grasslands would benefit for understanding AET spatial variations, which serves as a basis for regional water management. Based on published eddy covariance measurements in China, we collected AET values from 29 forests and 46 grasslands, and analyzed the differences in AET values and spatial variations between forests and grasslands in China. The results showed that forests had a significant higher AET (645.98 ± 232.73 kgH2O m-2 yr-1) than grasslands (359.31 ± 156.02 kgH2O m-2 yr-1), while the difference in AET values between forests and grasslands was not significant after controlling mean annual precipitation (MAP) relating factors. The effects of latitude and mean annual air temperature (MAT) on AET spatial variations differed between forests and grassland, while AET of forests and grasslands both exhibited increasing trends with similar rates along the increasing MAP, aridity index (AI), soil water content (SW), and leaf area index. The comprehensive effects of multiple factors on AET spatial variations differed between forests and grasslands, while MAP both played a dominating role. The effects of other factors were achieved through their close correlations with MAP. Therefore, forests and grasslands under similar climate had comparable AET values. AET responses to MAP were comparable between ecosystem types. Our findings provided a data basis for understanding AET spatial variation over terrestrial ecosystems of China or globally.